CaDHN4, a Salt and Cold Stress-Responsive Dehydrin Gene from Pepper Decreases Abscisic Acid Sensitivity in Arabidopsis - Zhang, Hua-feng; Liu, Su-ya; Ma, Ji-hui; Wang, Xin-ke; Haq, Saeed ul; Meng, Yuan-cheng; Zhang, Yu-meng; Chen, Ru-gang (International journal of molecular sciences, 2019)
Dehydrins play an important role in improving plant resistance to abiotic stresses. In this study, we isolated a dehydrin gene from pepper (Capsicum annuum L.) leaves, designated as CaDHN4. Sub-cellular localization of CaDHN4 was to be found in the nucleus and membrane. To authenticate the function of CaDHN4 in cold- and salt-stress responses and abscisic acid (ABA) sensitivity, we reduced the CaDHN4 expression using virus-induced gene silencing (VIGS), and overexpressed the CaDHN4 in Arabidopsis. We found that silencing of CaDHN4 reduced the growth of pepper seedlings and CaDHN4-silenced plants exhibited more serious wilting, higher electrolyte leakage, and more accumulation of ROS in the leaves compared to pTRV2:00 plants after cold stress, and lower chlorophyll contents and higher electrolyte leakage compared to pTRV2:00 plants under salt stress. However, CaDHN4-overexpressing Arabidopsis plants had higher seed germination rates and post-germination primary root growth, compared to WT plants under salt stress. In response to cold and salt stresses, the CaDHN4-overexpressed Arabidopsis exhibited lower MDA content, and lower relative electrolyte leakage compared to the WT plants. Under ABA treatments, the fresh weight and germination rates of transgenic plants were higher than WT plants. The transgenic Arabidopsis expressing a CaDHN4 promoter displayed a more intense GUS staining than the normal growth conditions under treatment with hormones including ABA, methyl jasmonate (MeJA), and salicylic acid (SA). Our results suggest that CaDHN4 can protect against cold and salt stresses and decrease ABA sensitivity in Arabidopsis.